Crowdsourcing the curriculum: Redefining e-learning practices through peer-generated approaches. Issue 2 (14th March 2016) - Paulin, Drew; Haythornthwaite, Caroline
ABSTRACT: Inclusion of open resources that employ a peer-generated approach is changing who learns what, from whom, and via what means. With these changes, there is a shift in responsibilities from the course designer to motivated and self-directed learner-participants. While much research on e-learning has addressed challenges of creating and sustaining participatory environments, the development of massive open online courses calls for new approaches that go beyond the existing research on participatory environments in institutionally defined classes. We decenter institutionally defined classes and broaden the discussion to the literature on the creation of open virtual communities and the operation of open online crowds. We draw on literatures on online organizing, learning science, and emerging educational practice to discuss how collaboration and peer production shape learning and enable "crowdsourcing the curriculum."